Taxonomic synopsis of the genus Tomarus Erichson, 1847 (Coleoptera: Scarabaeidae: Dynastinae) in Peru - López-García, Margarita M.; Giraldo-Mendoza, Alfredo E.; Deloya, Cuauhtémoc (Zootaxa, 2019)
We provided a taxonomic synopsis of the species of the genus Tomarus Erichson, 1847 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) of Peru. Diagnosis, illustrations, photographs, and maps are presented for each species and a taxonomic key to known species in the country is also included.